Analisis Kemampuan Penyelesaian Soal Matematika Siswa Kelas 3 MI Berdasarkan Gender - Fitria Agustin Indah Yulianti; Hamidulloh Ibda (Balai Diklat Keagamaan Semarang, 2025)
This study aims to produce a review of students' abilities in solving mathematical story problems from a gender perspective. The indicators of students' abilities in solving story problems used are the ability to record known information; the ability to record sought information; the ability to create mathematical models; the ability to solve mathematical models; and the ability to answer questions asked. The method used is quantitative through a cross-sectional survey. The subjects in this study were 23 third-grade students in the 2024/2025 academic year at MI Miftakhul Huda Temanggung. The results showed that female students' ability to solve math word problems was higher than that of male students, with an average difference of 7%. Although superior in recording the information sought and creating mathematical models, female students showed lower ability in solving mathematical models systematically and providing correct answers compared to male students. Meanwhile, in recording known information, both groups showed equal ability.